An essential guide to public speaking : serving your audience with faith, skill, and virtue - Schultze, Quentin J. (Quentin James), 1952- (2020)
"Communications expert Quentin Schultze offers a practical and accessible guide to public speaking, showing readers how to serve their audiences with faith, skill, and virtue. Now updated and expanded with new chapters"--
Includes bibliographical references.
Keywords: Rhetoric -- Religious aspects -- Christianity; Public speaking -- Religious aspects -- Christianity